Muscle specific miRNAs are induced by testosterone and independently upregulated by age - Nielsen, Søren; Hvid, Thine; Kelly, Meghan; Lindegaard, Birgitte; Dethlefsen, Christine; Winding, Kamilla; Mathur, Neha; Scheele, Camilla; Pedersen, Bente K.; Laye, Matthew J. (Frontiers in Physiology, 2014)
Age dependent decline in skeletal muscle function leads to impaired metabolic flexibility in elderly individuals. Physical activity and testosterone treatment have proven efficient strategies for delaying this condition. However, a common molecular pathway has not been identified. Muscle specific miRNAs (myomiRs) regulates metabolic pathways in skeletal muscle and are regulated by physical activity and have response elements for testosterone in their promoter region. We therefore hypothesized that myomiRs would be regulated in skeletal muscle during aging. We further investigated any potential gender-dependent regulation of these miRNAs. We found that the myomiRs miR-1, miR-133a and miR-133b were increased in skeletal muscle of elderly compared to younger men. In addition, miR-133a/133b expression was markedly higher in women compared to men. Elimination of circulating testosterone in men was associated with lower levels of miR-133a and miR-133b. A positive regulatory effect of testosterone on miR-133a/133b expression was confirmed in castrated male mice and in a model of primary human myocytes. Yet, an improvement of fitness level in the testosterone depleted men resulted in a down-regulation of miR133a/b. In conclusion, alterations in fitness level and circulating testosterone seem to represent two independent regulatory events where testosterone is a specific regulator of miR-133a/b expression.